The missing dead: late geometric burials at Lefkandi - Lemos, I (Meditarch Publishing, 2012)
Two Late Geometric burials discovered at Lefkandi are published in this paper. They belonged to children, and so far are the only evidence of burials dated to this period, filling a gap in our knowledge of funerary rites of this period at the site. The finds and their significance are discussed within the context of the Late Geometric Aegean. The important rite of enchytrismos for the burial of very young children and/or foetuses is discussed, and some suggestions are presented, regarding the wide spreading of the rites for the burial of the young.